Erythrocyte-cancer hybrid membrane-camouflaged melanin nanoparticles for enhancing photothermal therapy efficacy in tumors. (February 2019) - Jiang, Qin; Liu, Yao; Guo, Ranran; Yao, Xianxian; Sung, Seunghyun; Pang, Zhiqing; Yang, Wuli
Abstract: Cell membrane coating has emerged as an intriguing biomimetic strategy to endow nanomaterials with functions and properties inherent to source cells for various biomedical applications. Hybrid membrane of different types of cells could be coated onto nanoparticle surface to achieve additional functions. Herein, we fused red blood cell (RBC) membrane together with MCF-7 cell membrane and fabricated an erythrocyte-cancer (RBC-M) hybrid membrane-camouflaged melanin nanoparticle (Melanin@RBC-M) platform for enhancing therapeutic efficacy of photothermal therapy (PTT). The fused RBC-M hybrid membrane vesicles retained both RBC and MCF-7 cell membrane proteins and the resultant Melanin@RBC-M exhibited prolonged blood circulation and homotypic targeting to source MCF-7 cells simultaneously. Interestingly, increasing MCF-7 membrane components in RBC-M significantly enhanced the homotypic targeting function of Melanin@RBC-M while increasing RBC membrane components in RBC-M effectively reduced the cellular uptake of Melanin@RBC-M by macrophages and improved their circulation time in the blood. After intravenous injection into MCF-7 tumor-bearing athymic nude mice, Melanin@RBC-M with 1:1 membrane protein weight ratio of RBC to MCF-7 exhibited significantly higher tumor accumulation and better PTT efficacy compared with other Melanin@RBC-M with different membrane protein weight ratios as well as pristine melanin nanoparticles, due to the optimal balance between prolonged blood circulation and homotypic targeting. In addition, in vitro photoacoustic results revealed that Melanin@RBC-M had a photoacoustic signal enhancement with the increase of nanoparticle size (64 → 148 nm) and the photoacoustic amplitudes increased linearly with nanoparticle concentration at the excitation wavelength ranged from 680 nm to 800 nm, which could be used for quantification of Melanin@RBC-M in vivo . Looking forward, coating hybrid membrane onto nanoparticles could add flexibility and controllability in enhancing nanoparticles functionality and offer new opportunities for biomedical applications.